Interrelation and interference of policy and religion in the Republic of Kazakhstan - Baturin, V.S.; Baturina, L.L. (Ye.A.Buketov Karaganda State University Publ., 2014)
Kazakhstan has a special place in the process of preservation of peace and inter-ethnic, multicultural and interfaith harmony, which is given to interconnection and interaction of politics and religion. The article gives consideration to the fairly rich historical experience of display of the tolerance qualities of modern Kazakhs’ ancestors during their peaceful coexistence with the representatives of other ethnic groups as well as with representatives of different religions and believes. It is noted that the display of so-called «historical inversion» factor in the country resulted in a process, so to speak, of the religious Renaissance. However, at the same time, republic was uninsured against acts of various kinds of religious fanaticism, separatism, extremism, terrorism, etc. This means that the way of further development of Kazakhstan as a secular state, requires the policy of consolidation of all residents’ forces, in spite of their ethnicity or religion.
Қазақстан Республикасындағы дін жəне саясаттың өзара байланысы мен ықпалы
Взаимосвязь и взаимовлияние политики и религии в Республике Казахстан
Keywords: secular state; tolerance; freedom of conscience; freedom of religion; historical inversion; sect; totalitarian sect; religious fanaticism; separatism; extremism; terrorism